An AHP-Based Priority Selection Method for Capabilities Development: A Case Study of SDN Botok - Nisa'ul Fadhilah; Mutawakkillah, Nainunis; Anargiansyah, Muhammad Bagoes; Sari, Lelli Kurnia (Department of Physics, Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Surabaya (UNESA), 2025)
The critical investment of the future society needed to develop student capabilities for the early stage. Research has contributes considerably to the investigation of necessary student capabilities for improvement. However, previous studies typically focus on proposing a general of capabilities. There is limited knowledge of how a school can identify the necessary of student capabilities and plan the corresponding development program actions. This research aims to determine the capabilities that need to be developed in Botok elementary school use Gap Analysis and Analytical Hierarchy Process (AHP) method. The method supports the analysis of any factors that influence by identify the actual condition, pre-test and post-test assessment of student capabilities in Botok elementary school. The gap analysis results are presented that linguistic and spatial-visual capabilities has excellent category. Meanwhile, the mathematics has good category. This result of gap analysis reinforced by AHP method, that are the eigenvector value of linguistic capabilities (0,20), mathematics capabilities (0,71), and spatial-visual capabilities (0,09). Thus, finding this research shows that the mathematics capabilities are the most important to develop.